What Does It Take to Achieve Equality of Opportunity in Education? : An Empirical Investigation Based on Brazilian Data - Waltenberg, Fabio; Vandenberghe, Vincent (Les Cahiers de Recherche du Girsef, 2005)
Roemer’s’ 1998 seminal work on equality of opportunity has contributed to the emergence of a theory of justice that is modern, conceptually clear and easy to mobilize in policy design. In this paper, we apply Roemer’s theory to education policy. We first analyze the reallocations of educational expenditure required to equalize opportunities (taken to be test scores close to the end of compulsory education). Using Brazilian data, we find that implementing an equal-opportunity policy across pupils of different socio-economic background, by using per-pupil spending as the instrument, and ensuring that nobody receives less that 1/3 of the current national average, requires multiplying by 8.6 the current level of spending on the lowest achieving pupils. This result is driven by the extremely low elasticity of scores to per-pupil spending. As such, it implies large reallocations that are probably politically unacceptable. By exploiting our knowledge of the education production function we then identify ways of reducing financial reallocations needed to achieve equality of opportunity. We show that the simultaneous redistribution of monetary and nonmonetary inputs, like peer group quality (i.e., desegregation) and school effectiveness (i.e., equalizing access to the best-run schools), considerably reduces – by almost 50% – the magnitude of financial redistribution needed. Implementing an EOp policy would not come at any particular cost (or benefit) in terms of efficiency.